PEMASANGAN PIPA HDPE PADA PENYAMBUNGAN PIPA IRIGASI DENGAN METODE BUTT FUSION - Dery Syafrizal; W Widayat; Suseno Darsono (Jurnal Profesi Insinyur Indonesia, 2022)
This paper  was made based on the experience of implementing a network development project of the raw Spam Regional transmission pipeline BANJARBAKULA from IPA II Pinus (Kab. Banjar) to IPA Pramuka (Banjarmasin city). The path to be traversed installation of pipes not all can be accessed properly to mobilize pipes to  the location, until another alternative is found SO that HDPE pipe OD 710 mm to the location of the Pipeline installation plan, by the WAY of unwrapped HDPE pipe OD 710 mm in the irrigation channel primary Riam Kanan. Connection of HDPE pipe divided by two namely short circuit and long circuit with connection method using butt Fusion tool, until the pipe is connected to a single unit and hydrotest test results meet   the required specifications. Keywords : HDPE pipe OD 710 mm,  butt fusion,  curtain pipe, hydrotest